A brief review of multi objective optimization on nature-inspired method - Jonathan Likoh Juis @ Juise; Nona M. Nistah; Teong, Khan Vun; Hadzariah Ismail (Pusat e-pembelajaran, UMS, 2022)
Industrial change also known as development or industrial revolution pose challenges for optimisation. Most industrial optimisation problems involve multiple objectives, such as increases cost, use of valuable resources and time. Traditional methods are unable to solve modern multiobjective optimisation problems, where the new Priori Method has been proposed to overcome these problems. This paper presents some of the latest nature-inspired methods in multi-objective optimisation that have been proposed since 2010 to the present. It also aims to provide readers with new insights into the latest nature-inspired methods through providing a brief overview of the methods used by identifying them by their features and their evolution. Finally, the problems and challenges, future research and direction of nature-inspired methods in multi-objective optimisation will be discussed.